Managing lease portfolios : - Walker, Townsend (Wiley, 2006)
In Managing Lease Portfolios, Townsend Walker, an expert in this field, explains how to evaluate the risk of lease portfolios as well as hedge their long-term, non-traded risks. Here, you’ll learn how to apply various financial tools to your portfolio of leases and discover the work that goes into each step—such as measuring the risks of a lease, calculating the returns, and estimating the effects of diversification. Many of the ideas and concepts found within this comprehensive resource have existed for a number of years in the fields of foreign exchange, interest rate and credit derivatives, and the bond and stock markets. This book adapts and applies these concepts to managing leases. Then it illustrates how you can implement these new concepts through concrete models that have been proven to work in the real world.